PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Muhtar Hamin (Jurnal Inovasi Pendidikan dan Sains, 2021)
Classroom action research conducted at MAN 1 Lombok Timur Class X MIIA 2 Semester II aims to improve learning achievement in Mathematic subjects using the Student Team Achievement Division (STAD) Learning Model. The data from this research were collected by giving the Mathematic learning achievement test. In analyzing the data obtained, descriptive analysis method was used. The data generated from this study consisted of initial data, cycle I data and data from Cycle II. From the initial data, the average grade for the new class reached 67.35 and the learning completeness only reached 40%. This data is far below expectations considering that the KKM for Mathematic at this school is 75. In the first cycle there has been an increase and the percentage of learning completeness has reached 77%. In the second cycle, the average class acquisition has reached 85.35 and the percentage of learning completeness has reached 91,43%. The data in Cycle II is in line with expectations due to the use of a constructivist learning model. The conclusion obtained is the Student Team Achievement Division (STAD) Learning Model can improve Mathematic learning achievement for Class X Science 2 Semester II Academic Year 2020/2021 MAN 1 Lombok Timur.